Pedagogical practices and inclusion in school physical education: A study in Elementary Education in a full-time school (Research, Society and Development, 2026)
Education classes in a public full-time elementary school. It is based on the understanding that school inclusion goes beyond This article aims to analyze how pedagogical practices developed in Physical Education classes in elementary school, within a full-time public school context, may favor or hinder the inclusion of students with disabilities. The study is based on the understanding that school inclusion is not limited to access or enrollment, but also involves effective participation, permanence, and meaningful learning. The research is grounded in theoretical references that discuss inclusive education, teacher training, and inclusive Physical Education, drawing on authors such as Mantoan, Greguol, Martins, and Darido, as well as Brazilian educational legislation. The study adopts a qualitative and descriptive approach, carried out through classroom observations and the application of semi-structured questionnaires to fifteen Physical Education teachers from basic education. The results show that although there is recognition of the importance of inclusion, challenges remain related to initial and continuing teacher education, the lack of adequate pedagogical resources, and attitudinal and structural barriers present in the school environment. At the same time, pedagogical initiatives were identified that seek to adapt activities, make rules more flexible, and promote greater student participation. It is concluded that the consolidation of inclusive practices in Physical Education depends on strengthening teacher education, institutional commitment, and the development of a school culture that values diversity as an educational principle.